Uncertainties in adoption of model-based definition and enterprise for high-value manufacturing - Goher, Kamran; Shehab, Essam; Al-Ashaab, Ahmed; Sarfraz, Shoaib (IOS Press, 2021)
The world is adopting digital technologies at a rapid pace which are the key enablers to improve every walk of life in the modern era. This quest for digitization has equal rigor within the manufacturing industry. 2D drawings have been used historically to define the specifications of a product for manufacturing. The evolution in digital technologies has made it possible to improve the way of representing these specifications in the form of 3D models which is known as Model-Based Definition (MBD). However, the 2D representation is still the authoritative source within the industry for engineering definition and related documents in the product lifecycle. Though MBD has been adopted in design, discrete part manufacturing, and inspection stages to some extent, the industry heavily relies on the conventional 2D representation of product definition. The digitization process of product definition lies within the adoption of MBD as the authoritative source for all the enterprise activities which is referred to as Modelbased Enterprise (MBE). However, there are several uncertainties and risks in this process. In this work, it is ascertained to formulate the key uncertainties in the transformation towards MBD/E. These uncertainties are categorized and analyzed further for visualization.
Incorrect spelling of the author name in the paper: should be Ahmed Al-Ashaab.
Keywords: Model-Based Definition; Model-Based Enterprise; Uncertainties; Digital Manufacturing; Digital Thread; Digital Transformation